USE OF INNOVATIVE TECHNOLOGIES IN THE EDUCATIONAL ACTIVITY OF EDUCATIONAL ORGANIZATIONS - Egamberdiyev, Oyatillokh Alisher ugli; Maxamadjonov, Jakhongir Zokirjon ugli; Sobirova, Azizaxon Maribjon kizi (Educational Research in Universal Sciences, 2022)
Today it is difficult to imagine our life without modern technology. They are also very important in education. This article talks about the use of innovative technologies in the educational activities of educational organizations.